1965
DOI: 10.5006/0010-9312-21.3.84
|View full text |Cite
|
Sign up to set email alerts
|

Type 304 Stainless Steel vs Flowing CO2 At Atmospheric Pressure and 1100-1800F

Abstract: Oxidation characteristics of Type 304 stainless steel in CO2 were observed over the temperature range 1100–1800 F (593–982 C). Although in general oxidation rate curves were parabolic, several periods were observed in which they were approximately linear. These breaks were reproducible and thought to be associated with changes in rate-controlling step of the oxidation process. Carburization of Type 304 stainless steel during exposure to CO2 was observed. Several other alloys were studied, to determine earbiori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
1

Year Published

1970
1970
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 0 publications
1
36
0
1
Order By: Relevance
“…Fujii and Meussner [5] reported simultaneous oxidation and carburisation of Fe-Cr alloys containing 1-15 wt.% Cr in pure CO 2 at temperatures of 700, 900 and 1100°C. All alloys remained ferritic at 700°C and produced (Fe,Cr) carbides, the nature of which varied with alloy chromium content from (Fe,Cr) 3 C to (Fe,Cr) 7 C 3 and (Fe,Cr) 23 C 6 , in accordance with the Fe-Cr-C phase diagram. Carbon-containing austenite was formed at the higher temperatures and produced ferrite plus pearlite, martensite and/or (Fe,Cr) carbides upon cooling to room temperature, according to the alloy chromium content.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Fujii and Meussner [5] reported simultaneous oxidation and carburisation of Fe-Cr alloys containing 1-15 wt.% Cr in pure CO 2 at temperatures of 700, 900 and 1100°C. All alloys remained ferritic at 700°C and produced (Fe,Cr) carbides, the nature of which varied with alloy chromium content from (Fe,Cr) 3 C to (Fe,Cr) 7 C 3 and (Fe,Cr) 23 C 6 , in accordance with the Fe-Cr-C phase diagram. Carbon-containing austenite was formed at the higher temperatures and produced ferrite plus pearlite, martensite and/or (Fe,Cr) carbides upon cooling to room temperature, according to the alloy chromium content.…”
Section: Introductionmentioning
confidence: 66%
“…Internal carbides were observed after exposure of 9Cr (P92) and 12Cr (X20 and VM12) steels to Ar-50%CO 2 at 550°C [1], and after exposure of model Fe-Cr alloys to Ar-30%CO 2 at 650°C [2]. Reaction of pure CO 2 with an 18Cr (304) steel at 704, 816 and 927°C [3] and with an Fe-15Cr alloy at 900°C [4] also led to internal carbide precipitation. Fujii and Meussner [5] reported simultaneous oxidation and carburisation of Fe-Cr alloys containing 1-15 wt.% Cr in pure CO 2 at temperatures of 700, 900 and 1100°C.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Gilewicz-Wolter (8) has also shown that during the oxidation of iron in SOz atmospheres transport of sulphur takes place via preferred paths at low sulphur dioxide partial-pressure, whereas at one atmosphere fissures are produced at the corners of the specimens through which sulphur from the atmosphere penetrates the scale. McCoy (9) proposed that the carburization of chromium steels in flowing C 0 2 atmospheres at high temperatures may be due to the accumulation of COz molecules in pores present in the outer oxide layer. Birks ( 1 0) proposes that the metal ions and electrons diffusing outwards t o the scale-gas interface produce metal oxide and carbon monoxide which then diffuses inward down microcracks to the porous region of the scale where the CO/CO2 redox system is established.…”
Section: Introductionmentioning
confidence: 99%
“…Future power plants are theoretical to work in the range of 700 °C. The technologies with CO 2 environment require increasing efficiencies which cause higher working temperatures, pressure and customized gas compositions [5]. As that reason, better understanding of the corrosion behaviour of the materials react with CO 2 and H 2 O has to be obtained.…”
Section: Introductionmentioning
confidence: 99%